Measuring the Probability of Prohibition of the Spread of Wahhabism in Indonesia Based on Positive Law - Suhli, Suhli; Hatta, Mohammad (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
The increasingly massive spread of Wahhabi ideology in Indonesia has given rise to reactive reactions among society, this is because Wahhabi preaching emphasizes the labeling of Bid'ah and Infidels towards other communities who have different understandings, and this has implications for the many horizontal conflicts that occur during public. Even though Indonesian society is known as a harmonious society amidst diversity and religion. This research is descriptive research with a qualitative approach, while the data collection technique used is a literature study. Then the data collected through the study of the text was compiled, then analyzed using the descriptive analysis method with a deductive mindset. The results of this research are that the Wahhabi ideology pioneered by Muhammad bin Abdul Wahab is an understanding that is oriented towards purifying the creed, which at that time was considered to have experienced many setbacks along with the development of the tarekat's teachings. However, the movement for this understanding is often accompanied by doctrines of heresy, syrk, and infidelity which create polarization in society. In this position, the state constitutionally regulates that every society has the right to believe in beliefs and express thoughts and attitudes following their conscience, but if these beliefs and statements of belief are carried out by causing divisions in society, then this is where the role of the State is needed to ensure peace. and the harmony that is the identity of the Indonesian nation is maintained, meaning that there needs to be a firm stance from the government regarding the spread of Wahhabi ideology, and the Perppu is an alternative as well as a legal instrument that is very possible for the Government to implement to stop the spread of Wahhabi ideology in Indonesia and at the same time reflects this attitude. The government is firm against anyone who destroys the diversity of Indonesian society Keywords: Wahabi, Labeling, Horizontal Conflict